Fabrication of cation exchange membrane from polyvinyl alcohol using lignin sulfonic acid: Applications in diffusion dialysis process for alkali recovery. Issue 6 (13th April 2017) - Afsar, Noor Ul; Yu, Dongbo; Cheng, Congliang; Emmanuel, Kamana; Ge, Liang; Wu, Bin; Mondal, Abhishek N.; Khan, Muhammad Imran; Xu, Tongwen
ABSTRACT: We report polyvinyl alcohol (PVA)-based hybrid membranes composed of salt of lignin sulfonic acid (LSA) and tetraethyl orthosilicate. The concentration of LSA with respect to PVA varied from 10% to 40%. The hybrid membranes showed water uptake ( W U ) in the range of 122–210%, ion exchange capacities in the range of 0.32–0.75 mmol g −1, dialysis coefficient ( U OH ) from 0.0068 to 0.0119 m h −1, and selectivity ( S ) from 15 to 26. The hybrid membranes also showed thermal and mechanical stability.